1999
DOI: 10.1038/sj.onc.1202839
|View full text |Cite
|
Sign up to set email alerts
|

The myb gene family in cell growth, differentiation and apoptosis

Abstract: The myb gene family consists of three members, named A, B and c-myb which encode nuclear proteins that function as transcriptional transactivators. Proteins encoded by these three genes exhibit a tripartate structure with an N-terminal DNA-binding domain, a central transactivation domain and a C-terminal regulatory domain. These proteins exhibit highest homology in their DNA binding domains and appear to bind DNA with overlapping sequence speci®cities. Transactivation by myb gene family varies considerably dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
394
1
5

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 453 publications
(409 citation statements)
references
References 178 publications
(154 reference statements)
9
394
1
5
Order By: Relevance
“…The Myb proto-oncogene was first identified as the cellular homolog of two replication-defective acute transforming avian retroviruses, AMV and E26, that cause myeloblastic and erythroblastic leukemias (Radke et al, 1982;Oh and Reddy, 1999). Expression of c-Myb is predominantly associated with immature hematopoietic cells.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Myb proto-oncogene was first identified as the cellular homolog of two replication-defective acute transforming avian retroviruses, AMV and E26, that cause myeloblastic and erythroblastic leukemias (Radke et al, 1982;Oh and Reddy, 1999). Expression of c-Myb is predominantly associated with immature hematopoietic cells.…”
Section: Introductionmentioning
confidence: 99%
“…Three distinct functional domains have been identified on c-Myb: a DNA-binding domain (DBD), a transactivation domain (TA) and a negative regulatory domain (NRD) (Oh and Reddy, 1999). The c-Myb DBD is located at the amino-terminus and is a highly conserved region consisting of three tandem repeats of approximately 50 amino acids each (R1, R2 and R3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This data imply that a large fraction of the human population is carrier of B-MYB alleles that might be associated with a reduced risk of developing neoplastic disease. Oncogene (2008Oncogene ( ) 27, 2929Oncogene ( -2933doi:10.1038/sj.onc.1210947;published online 19 November 2007 Keywords: transcription; neuroblastoma; colon cancer; leukaemia; apoptosis B-MYB is a putative proto-oncogene required for mammalian development and involved in cell proliferation and survival (Oh and Reddy, 1999;Tanaka et al, 1999;Sala, 2005). Although there is still no evidence of its direct involvement in human cancer, several studies have revealed that B-MYB is either amplified or overexpressed in different human malignancies, while its expression in neuroblastoma patients correlates with poor survival (Raschella et al, 1999;Forozan et al, 2000;Tanner et al, 2000;Bar-Shira et al, 2002).…”
mentioning
confidence: 99%
“…Aberrant B-MYB expression might promote cancer development through increased activity of downstream target genes. B-MYB target genes have been found that promote cell cycle progression or resistance to apoptosis, although B-MYB effects might also occur through other mechanisms (Oh and Reddy, 1999;Sala, 2005). While the above described studies support the hypothesis that B-MYB is a proto-oncogene, a recent report shows that an inactivating mutation of B-MYB in zebrafish actually promotes chemical carcinogenesis as a consequence of genomic destabilization (Shepard et al, 2005).…”
mentioning
confidence: 99%